Potential of Nigella sativa as a Natural Antimicrobial Drug Candidate: Potensi Nigella sativa sebagai Kandidat Obat Antimikroba Alami - Kareem , Alswedawi Wissam; kareem , Alswedawi Husham; Nouri , Saif subhy (Academia Open, 2025)
General Background: Antibiotic resistance has emerged as a major global health crisis in recent decades, driven by the rise of multi-drug resistant pathogens. Specific Background: As conventional antibiotics become less effective, there is growing interest in exploring natural sources, such as medicinal plants, for novel antimicrobial agents. Knowledge Gap: Despite the traditional use of Nigella sativa in various cultures, the precise mechanisms underlying its antimicrobial properties remain inadequately understood. Aims: This mini-review aims to highlight the potential of Nigella sativa seeds and oil as promising antimicrobial agents, focusing on their bioactive compounds and therapeutic applications. Results: Findings indicate that the therapeutic potential of N. sativa is largely attributed to thymoquinone and other key constituents, including linoleic acid, nigellone, nigilline, melanthin, and trans-anethole, which exhibit diverse pharmacological activities such as antimicrobial, anti-inflammatory, antioxidant, and gastroprotective effects. Novelty: This review underscores the relevance of N. sativa as a safe, natural alternative in antimicrobial therapy, rooted in traditional medicine yet supported by emerging scientific evidence. Implications: Future research should focus on elucidating the molecular mechanisms of N. sativa’s bioactivity and isolating specific active compounds to facilitate drug development against resistant pathogens. Highlights: Rising antibiotic resistance demands alternative antimicrobial sources. Nigella sativa shows therapeutic potential via thymoquinone and key compounds. Supports future drug development from natural, plant-based bioactive agents. Keywords: Nigella sativa; Black seed ; Antibacterial; Antibiotics resistance